2021
DOI: 10.1039/d1ra00424g
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and phosphorus co-doped nickel–cobalt layered double hydroxides for enhancing electrochemical reactivity and supercapacitor performance

Abstract: The optimized sulfur and phosphorus co-doped NiCo LDH reduces charge transfer resistance and realizes efficient redox reaction, achieving an outstanding specific capacitance of 3844.8 F g−1 at 3 A g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 61 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…Developing binder-free electrodes is not the only way to improve the capacitive performance of the desired electroactive material. An alternate effective approach is the incorporation of heteroatom doping with dissimilar atomic radii as well as suitable anchoring of the electroactive material on the template surface. , Theoretical and experimental calculations showed that the addition of anions (O, S, and Se) can regulate the overall electronic structure, upsurge the electronic conductivity of the material, and provide effective bridging between the template and electroactive materials, which is worthy of electrochemical energy storage. , It has also been scrutinized that Se-containing hybrid materials not only rejuvenate the rate capacity but also provide a superior cycle life because of its low ionization energy, high electronic conductivity, and better metallic properties compared to those of S and O. , In addition, Se-infiltrated TMP has the high synergistic effect among TMPs and Se, which can directly affect OH – ion adsorption of the surface. Thus, the modification of NiCoP along with 1D CNF via Se anchoring can easily modulate the electronic structure and density of states, which play a significant role in assisting the electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Developing binder-free electrodes is not the only way to improve the capacitive performance of the desired electroactive material. An alternate effective approach is the incorporation of heteroatom doping with dissimilar atomic radii as well as suitable anchoring of the electroactive material on the template surface. , Theoretical and experimental calculations showed that the addition of anions (O, S, and Se) can regulate the overall electronic structure, upsurge the electronic conductivity of the material, and provide effective bridging between the template and electroactive materials, which is worthy of electrochemical energy storage. , It has also been scrutinized that Se-containing hybrid materials not only rejuvenate the rate capacity but also provide a superior cycle life because of its low ionization energy, high electronic conductivity, and better metallic properties compared to those of S and O. , In addition, Se-infiltrated TMP has the high synergistic effect among TMPs and Se, which can directly affect OH – ion adsorption of the surface. Thus, the modification of NiCoP along with 1D CNF via Se anchoring can easily modulate the electronic structure and density of states, which play a significant role in assisting the electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Table S2 shows that increasing the urea concentration to 0.08 M (NMP-4) gradually increases the surface area, pore volume, and pore diameter, while the trend is reversed with a further increase of the urea concentration. The enhanced surface area with a high pore volume (and a drastic increase in the pore diameter) of the NMP-4 sample might be due to the dominance of microplate-like architectures with good mesoporosity, leading to improved electrolytic charge storage and ion transport and, ultimately, can result in enhanced supercapacitor features. , …”
Section: Resultsmentioning
confidence: 99%
“…119 Kim et al developed an S and P co-doping strategy to enhance the electrocatalytic activity and supercapacitor performance of NiCo-LDH. 120 S and P co-doping can regulate the morphology of NiCo-LDH nanoarray (NiCo-LDH-SP). The heterogeneous porous structure effectively reduces charge transfer resistance, which achieves a rapid and efficient Faraday reaction.…”
Section: Non-metal Co-dopingmentioning
confidence: 99%